Decitabine regulates the resistance of HCC to sorafenib through demethylation - Miao Zhang; Xiaolei Zhou; Zhenzhen Li; TianYu Zhao; Yu Miao; Sen Liu; Qiaoqiao Han; Libo Wang; Yongdeng Xu; Tao Cui; Ze Wang; Xiulin Yi; et al. (Clinical Epigenetics)
Abstract Purpose To evaluate the efficacy of sorafenib in combination with the DNA methylation inhibitor decitabine (DAC) for the treatment of hepatocellular carcinoma (HCC), and to investigate the mechanism of sorafenib resistance from an epigenetic perspective, aiming to provide new insights and strategies for HCC therapy. Methods The GEPIA2 database was used to analyze the expression of solute carrier organic anion transporter family member 1B3 (SLCO1B3) in various tumors and adjacent normal tissues. The Kaplan–Meier method was applied to assess the relationship between SLCO1B3 expression and overall survival. The Cancer Genome Atlas (TCGA) Liver Hepatocellular Carcinoma (LIHC) dataset was used to analyze correlations between SLCO1B3 and DNA methyltransferases (DNMTs). Methylation levels of the SLCO1B3 promoter in Hep3B, HepG2, SNU182, and SNU387 cells were determined by bisulfite sequencing PCR. The expression of organic anion transporting polypeptide 1B3 (OATP1B3), encoded by SLCO1B3, was measured by RT-qPCR and Western blot. The effect of sorafenib combined with DAC on Hep3B and HepG2 cells proliferation was dynamically monitored using the Agilent xCELLigence Real-Time Cell Analysis eSight system (RTCA-eSight). The mechanism was further validated in vivo using a Hep3B xenograft model in nude mice. OATP1B3 expression in tumor tissues was examined by immunohistochemistry and Western blot. Results HCC patients with high SLCO1B3 expression had significantly better overall survival than those with low expression. SLCO1B3 expression was negatively correlated with DNMTs expression. Compared to other HCC cell lines, Hep3B and HepG2 cells exhibited higher DNA methylation levels and lower OATP1B3 protein expression. DAC treatment upregulated OATP1B3 expression in Hep3B and HepG2 cells. Co-administration of DAC increased sorafenib uptake and enhanced its cytotoxic effect in these cells. In the Hep3B xenograft model, tumor volumes in the combination group were markedly smaller than those in the monotherapy and control groups. OATP1B3 expression was significantly higher in both the combination and DAC-only groups compared to the control and sorafenib-only groups. Conclusion DAC promoted OATP1B3 expression by inhibiting SLCO1B3 methylation, thereby enhancing HCC sensitivity to sorafenib. These findings may offer novel therapeutic strategies for the clinical management of HCC.